Practical numerical analysis using microsoft Excel - Nandy, A. (Alpha Science international Limited, 2004)
This text presents numerical analysis in an easy and lucid manner requiring no prior knowledge of computer programming or intricacies of mathematics using MS-EXCEL 2000. The analysis used can also be done using earlier versions of MS-Excel. The majority of numerical analysis needs fall into the curve fitting, interpolation, solutions of equations and integration methods. For these Excel's features provide a very easy and inexpensive way to get the job done. Key features of this book include: a number of problems, illustrations and exercises; and illustrative examples from contemporary fields such as environment, theoretical biology and biophysics